Informasi dalam Perspektif Islam - Kahfi, Agus Sofyandi (Mediator, 2006)
Today we faced an increasing number and forms of information delivered from media channels throughout the world. The speed of change and the reach of (tele)communication technology has shaped a new way of communication methods, new audience behavior, which in turn also created a new cultural landscape. In Islamic perspective, information and communication activities were perceived as a way to deliver thoughtful and moral messages to people. The essence of communication lies in the process of expressing message effectively by communications facilities. Communication must be done repeatedly in order to reach intended effects. A communicator, therefore, has to acquire basics of communication method to touch his/her audience. This article points out some basics of Islamic communication which are no different with the principles of general communication.